ENGLISH AS A MEDIUM OF INSTRUCTION: LANGUAGE LEARNING STRATEGIES EMPLOYED BY ENGLISH LANGUAGE LEARNERS IN LIBYA (Journal of Academic Research, 2018)
Recent researches on English as a Second/ Foreign Language (ESL/EFL) have focused on learner-centered behavior, which consequently have led to the study of the identification of learning strategies. This has become significant in language teaching and learning environment. Thus, learning strategies are useful tools to enhance learners’ language acquisition, capitalizing on the language inputs they receive in the classroom.                           In the current study, the participants are from Arabic medium background, pursuing their higher studies in English medium of instruction. At university level, English is to a greater extent the primary vehicle for the classroom input, but not for the daily interaction. Consequently, this in some ways affect learners' outputs and restrict their learning of the target language. It has been claimed that, in a foreign language learning setting, language learning styles and strategies are considered as a crucial factor to determine the effectiveness of students’ learning and interaction.               This study aims to investigate the various strategies adopted by undergraduate Libyan learners to cope with English medium of instruction at university level. The learners, it must be noted, use specific techniques that could lead them towards self-directed and autonomous learning. For, the basic aim of the English language education at a higher level is to make the learners independent and to fully appreciate the language.